Artist to co-represent Greece in Prague Quadrennial - Volanakis, Adonis (My University, 2026)
Chosen Artist by a committee (12 members) to co-represent Greece in Prague Quadrennial / Ministry of Culture of Greece
Keywords: Arts and entertainment